Viral miRNAs Alter Host Cell miRNA Profiles and Modulate Innate Immune Responses - Naqvi, Afsar R.; Shango, Jennifer; Seal, Alexandra; Shukla, Deepak; Nares, Salvador (Frontiers in Immunology, 2018)
Prevalence of the members of herpesvirus family in oral inflammatory diseases is increasingly acknowledged suggesting their likely role as an etiological factor. However, the underlying mechanisms remains obscure. In our recent miRNA profiling of healthy and diseased human tooth pulps, elevated expression of human herpesvirus (HHV) encoded v-miRs were identified. Based on the fold induction and significance values, we selected three v-miRs namely miR-K12-3-3p (Kaposi sarcoma-associated virus [KSHV]), miR-H1 (herpes simplex virus 1 [HSV-1]), and miR-UL-70-3p (human cytomegalovirus [HCMV]) to further examine their impact on host cellular functions. We examined their impact on cellular miRNA profiles of primary human oral keratinocytes (HOK). Our results show differential expression of several host miRNAs in v-miR transfected HOK. High levels of v-miRs were detected in exosomes derived from v-miR transfected HOK as well as the KSHV infected cell lines. We show that HOK derived exosomes release their contents into macrophages (Mφ) and alter expression of endogenous miRNAs. Concurrent expression analysis of precursor (pre)-miRNA and mature miRNA suggest transcriptional or post-transcriptional impact of v-miRs on the cellular miRNAs. Employing bioinformatics, we predicted several pathways targeted by deregulated cellular miRNAs that include cytoskeletal organization, endocytosis, and cellular signaling. We validated three novel targets of miR-K12-3-3p and miR-H1 that are involved in endocytic and intracellular trafficking pathways. To evaluate the functional consequence of this regulation, we performed phagocytic uptake of labelled bacteria and noticed significant attenuation in miR-H1 and miR-K12-3-3p but not miR-UL70-3p transfected primary human Mφ. Multiple cytokine analysis of E. coli challenged Mφ revealed marked reduction of secreted cytokine levels with important roles in innate and adaptive immune responses suggesting a role of v-miRs in immune subversion. Our findings reveal that oral disease associated v-miRs can dysregulate functions of key host cells that shape oral mucosal immunity thus exacerbating disease severity and progression.